COMPREHENSIVE TEST ITEMS ANALYSIS OF TEACHER-MADE ENGLISH SUMMATIVE ASSESSMENT IN THIRD GRADE PRIMARY SCHOOL - Wibowo, Enggar Pangesti (Journal of English Educational Study (JEES), 2025)
Summative test is a written test given at the middle or end of the semester. This study aims to investigate the overall quality of a teacher-made English summative test at one of private Islamic elementary school in Semarang, Central Java, using the general and specific guidelines set for constructing good test items. This research offers a document analysis of a qualitative study involving teacher-made test at primary school level that remains under-explored. The study reveals that the test instrument consists of single and complex multiple-choice questions, short answers and essays that assess the students’ ability in vocabulary, grammar, and simple sentences. The test items generally meet most of the aspects of the principles, but some aspects require further attention such as the use of correct punctuation and spelling, clear, contextualised and functional images, and appropriate grammar. In particular, the options in single-choice and complex multiple-choice questions should be organised homogeneously. For short answer questions, it is necessary to ensure that each question has one correct answer. On the essay questions, no significant problems were found. Revisions are needed to enhance the quality of the test. Accordingly, this study provides valuable insights and improvement recommendations to address aspects that become concerns.